2017
DOI: 10.9789/2175-5361.2017.v9i2.495-502
|View full text |Cite
|
Sign up to set email alerts
|

Sexualidade de pacientes com estomias intestinais de eliminação Sexuality of patients with bowel elimination ostomy

Abstract: How to quote this article: Vera SO; Sousa GN; Araújo SNM; et al. Sexuality of patients with bowel elimination ostomy. Rev Fund Care Online. 2017 abr/jun; 9(2):495-502. DOI: http://dx.doi.org/10. 9789/2175-5361.2017.v9i2.495-502 ABSTRACT Objective: To evaluate the impact of ostomy in the sexuality of an stomized individual. Methods: A descriptive exploratory study with a quantitative approach, developed in an Integrated Health Center in Teresina/PI. Eighty three patients participated, according to the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
3
4
0
8
Order By: Relevance
“…Regarding marital status, most were married and the self-reported skin color was brown, results that corroborate similar studies 16,17 . Although most are married, there is a feeling of fear and insecurity regarding the partner, due to the new condition in which they find themselves physically, living with the stoma and the collecting equipment generate psychological and emotional problems, bringing feelings of shame and lack of sexual interest 14,16 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding marital status, most were married and the self-reported skin color was brown, results that corroborate similar studies 16,17 . Although most are married, there is a feeling of fear and insecurity regarding the partner, due to the new condition in which they find themselves physically, living with the stoma and the collecting equipment generate psychological and emotional problems, bringing feelings of shame and lack of sexual interest 14,16 .…”
Section: Discussionsupporting
confidence: 87%
“…With regard to education level, there was a predominance of low education, as in other similar studies 14,16,20 .…”
Section: Discussionsupporting
confidence: 78%
“…The study also pointed out that changes in sexuality are associated with body image and affect esteem as well as interpersonal interaction with the significant person, family, and friends. These situations also confirm the findings of this review, in which the results identified the occurrence of reduced desire, dissatisfaction with sexual life, reduced sexual encounters, marital adjustments, changes in behaviors related to sexuality (44) such as changes in sexual positions, lack of desire or reduction of interest, which can evolve to inactivity or even rejection (14) .…”
Section: United Statessupporting
confidence: 85%
“…Impacts on the quality of sexual life with the appearance of sexual dysfunction, changes in impulse, sex arousal, orgasm, and sexual satisfaction Sexuality of patients with bowel elimination ostomy (14) 2017 Brazil…”
Section: Resultsmentioning
confidence: 99%
“…Com relação ao estado civil, a maioria era casada e a cor da pele autodeclarada foi parda, resultados que corroboram estudos semelhantes 16,17 . Apesar de a maioria ser casada, existe um sentimento de medo e insegurança com relação ao parceiro, devido à nova condição em que se encontra fisicamente, a convivência com a estomia e o equipamento coletor geram problemas psicológicos e emocionais, trazendo sentimento de vergonha e desinteresse sexual 14,16 .…”
Section: Discussionunclassified